Assessing the effects of environmental factors on filtration rate of golden mussel (Limnoperna fortunei) - Zhang, Jiahao; Xu, Mengzhen; Yang, Yao (Ecological indicators, 2024)
[Display omitted] •Systematic experiments were performed to study influence of environmental factors on golden mussel’s filtration rate.•A mussel pump model that combined physiological and physical process was developed.•The model shows superior mechanical explanations and better accuracy performance compare to previous statistical models. Filtration rate is a crucial characteristic for bivalves that engage in filter feeding, and is subject to regulation in response to various environmental factors. Golden mussel, Limnoperna fortunei, known as intensively invasive species in South America and many Asian regions, has been observed to exhibit a wide range of filtration rate, resulting in challenges in hydraulic modeling and impact assessment. In this study, we performed a series of experiments and developed a mussel pump model to assess the filtration rate of golden mussels with different shell lengths and to investigate the impact of environmental factors that influence the filtration rate, i.e., food type, water temperature, and flow condition. We found that filtration rates increased with shell length, while filtration rates per unit weight decreased with shell length. Additionally, we observed that filtration rates were comparable when the mussels were fed with food that share similar/identical cellular properties, e.g., Saccharomyces cerevisiae and Chlorella pyrenoidosa. The temperature's effect on filtration rates followed a skewed unimodal pattern, with an optimal temperature near 20 ℃. Interestingly, the experiments also showed that the golden mussel can filter at low temperatures (2 ℃), indicating its capacity for overwinter survival in cold regions. Moreover, the golden mussel's filtering was promoted under low-velocity flowing conditions. The relationship between filtration rate and multiple factors was explicable using our pump mussel model, which could be simplified to reveal the effect of each single factor. The model shows superior mechanical explanations and better accuracy performance compare to previous statistical models.